"Why Don't You Reach Out to Dad?": Involving Fathers in Therapy. (November 2021) - Thomas, Alvin; Lee, Jocelyn R. Smith; Muhammed, Michael; Caldwell, Cleopatra H.
Purpose: The literature indicates that engaging fathers in family therapy improves children's mental health outcomes; however, clinicians are generally ill prepared for this challenge. Method: This qualitative study applies multiple case-study design to focus group data addressing social worker's training experiences and attitudes toward involving fathers in therapy. Results: From an analysis of qualitative data from 14 social workers in training, three themes are discussed: (1) clinician exposure to nonresident fathers and their perceptions of the role of fathers in families, (2) barriers experienced in engaging fathers in the therapeutic process, and (3) training to work with nonresident fathers. Discussion: The themes are discussed with sample responses from representative participants and training areas. The findings suggest areas of focus for clinician training and practice such as modeling in session strategies, providing supervision and consultation, adjusting institutional policy, and offering additional course work and seminars that encourage and scaffold father engagement.